Legal liability of livestock owners for accidents on public roads in Aceh Jaya - Daniel Fajri, Muhammad; Nasution, Anhar; Aguswandi, Putra; Wiratmadinata, Wiratmadinata (Geuthèë Institute, Aceh, 2025)
This study explores the legal liability of livestock owners for traffic accidents caused by wandering animals on public roads in Aceh Jaya Regency. The background of the study is the increasing number of road accidents involving livestock, which not only endanger road users but also reflect weak implementation of local regulations. Although Qanun No. 11 of 2021 on Livestock Control has been enacted as a legal instrument to regulate and enforce animal ownership responsibilities, its implementation is still far from optimal. The problem lies in the legal gap between the formal norms stated in the qanun and the customary legal practices that dominate in the community. This research uses an empirical juridical method by combining normative analysis with field data through interviews with livestock owners, accident victims, law enforcement officers, and local government officials. The findings reveal that legal responsibility is often resolved through informal channels such as family deliberation or customary sanctions, which are not recorded as formal legal processes. The lack of public legal awareness, weak law enforcement, absence of livestock identification systems, and limited infrastructure have hindered the enforcement of the qanun. Meanwhile, the local government has made several efforts, including socialization, animal impoundment, auctions, and applying administrative and criminal sanctions. However, these efforts still face structural and cultural challenges. Therefore, to optimize livestock control and reduce accidents, this study recommends a more integrated approach involving the synchronization of formal and customary laws, digital registration of livestock, development of collective livestock shelters, and strengthening public legal education. This research contributes to the discourse on legal accountability in decentralized governance areas and emphasizes the need for regulatory reform that is sensitive to local socio-cultural contexts. A collaborative model involving local governments, traditional leaders, and civil society is essential for creating an effective and sustainable legal framework to protect public safety on roads